Matematyka

Autorzy:Maciej Antek, Krzysztof Belka, Piotr Grabowski

Wydawnictwo:Nowa Era

Rok wydania:2015

Rozwiąż nierówność 4.61 gwiazdek na podstawie 13 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`-3(x-3)^2+(-3x+3 1/2)^2>=6(x+1)^2+0,25` 

`-3(x^2-6x+9)+(-3x+7/2)^2>=6(x^2+2x+1)+1/4` 

`-3x^2+18x-27+9x^2-21x+49/4>=6x^2+12x+6+1/4`  

`6x^2-3x-27+12 1/4>=6x^2+12x+6 1/4\ \ \ |-6x^2` 

`-3x-27+12 1/4>=12x+6 1/4\ \ \ |-6 1/4` 

`-3x-27+6>=12x` 

`-3x-21>=12x\ \ \ |+3x` 

`-21>=15x\ \ \ |:15` 

`-21/15>=x` 

`-7/5>=x` 

`x<=-7/5` 

`x<=-1 2/5` 

 

Największa liczba całkowita, która spełnia tą nierówność, to -2.